Borderline personality disorder - Gunderson, John G.; Herpertz, Sabine (Nature reviews. Disease Primers, 2018)
Caretakers are often intimidated or alienated by patients with borderline personality disorder (BPD), compounding the clinical challenges posed by the severe morbidity, high social costs and substantial prevalence of this disorder in many health-care settings. BPD is found in ∼1.7% of the general population but in 15-28% of patients in psychiatric clinics or hospitals and in a large proportion of individuals seeking help for psychological problems in general health facilities. BPD is characterized by extreme sensitivity to perceived interpersonal slights, an unstable sense of self, intense and volatile emotionality and impulsive behaviours that are often self-destructive. Most patients gradually enter symptomatic remission, and their rate of remission can be accelerated by evidence-based psychosocial treatments. Although self-harming behaviours and proneness to crisis can decrease over time, the natural course and otherwise effective treatments of BPD usually leave many patients with persistent and severe social disabilities related to depression or self-harming behaviours. Thus, clinicians need to actively enquire about the central issues of interpersonal relations and unstable identity. Failure to correctly diagnose patients with BPD leads to misleading pharmacological interventions that rarely succeed. Whether the definition of BPD should change is under debate that is linked to not fully knowing the nature of this disorder.
Gesehen am 16.05.2019